Stanley Cavell and the Education of Grownups - Standish, Paul, 1949-; Saito, Naoko (Book collections on Project MUSE., 2012)
What could it mean to speak of philosophy as 'the education of grownups'? This book takes Cavell's enigmatic phrase as a provocation to explore the themes of education that run throughout his work - from his response to Wittgenstein, Austin and ordinary-language philosophy, to his readings of Thoreau.